Complementary DNA Cloning and Functional Characterization of Cytochrome P450 3A138 in Common Carp (Cyprinus carpio L.). Issue 6 (12th March 2014) - Ma, Junguo; Bu, Yanzhen; Li, Yao; Niu, Daichun; Li, Xiaoyu
ABSTRACT The full‐length sequence of a cytochrome P450 3A 138 (CYP3A138) cDNA in common carp was cloned and sequenced. The transcriptional and microsome enzyme activities of CYP3A138 in the fish liver after rifampicin exposure were also determined in this study. The results showed that the full‐length CYP3A138 cDNA is 1912 base pairs (bp) long and contains an open reading frame of 1551 bp encoding a protein of 517 amino acids. Sequence analysis revealed that CYP3A138 is highly conserved in fish. Furthermore, the results of quantitative real‐time PCR revealed that CYP3A138 in common carp is constitutively expressed in all tissues, but mainly in the liver and intestine. Additionally, rifampicin exposure promoted both the expression of CYP3A138 at the transcriptional level and the activity of the protein, suggesting that CYP3A138 is a member of the CYP3A subfamily.